'How did we get to where we are now?' Reflecting on Stuart Hall in Birmingham. Issue 1 (2nd January 2018) - Hussain, Ajmal
ABSTRACT: In this piece I reflect on the city of Birmingham – as one trajectory in Stuart Hall's life among the many described in Familiar Stranger – for the significance it holds in terms of the development of race theory in the UK. Birmingham is often remembered among students, activists and scholars working or interested in the areas of race, ethnicity and culture, as the place that hosted Stuart Hall and the Centre for Contemporary Cultural Studies (CCCS) over half a decade ago. Here I consider the charged atmosphere of race relations associated with this period and place and how this marked a point of suture in Hall's thinking so far. I end by reflecting on the significance this has had in shaping the field of race and ethnic relations in ways that were significant then and now.